2013
DOI: 10.3390/md12010088
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lionfish (Pterois volitans): A Potential Human Health Threat for Ciguatera Fish Poisoning in Tropical Waters

Abstract: Invasive Indo-Pacific lionfish (Pterois volitans) have rapidly expanded in the Western Atlantic over the past decade and have had a significant negative impact on reef fish biodiversity, habitat, and community structure, with lionfish out-competing native predators for resources. In an effort to reduce this population explosion, lionfish have been promoted for human consumption in the greater Caribbean region. This study examined whether the geographical expansion of the lionfish into a known ciguatera-endemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…Both the present study and that of Robertson et al (2014) are in agreement over the lack of correlation between body weight and toxin content. Earlier hypothesis regarding the transfer of CTXs through the food web considered larger fish to be more hazardous (Randall, 1958).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Both the present study and that of Robertson et al (2014) are in agreement over the lack of correlation between body weight and toxin content. Earlier hypothesis regarding the transfer of CTXs through the food web considered larger fish to be more hazardous (Randall, 1958).…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with the study by Robertson et al (2014) that identified CTXs in lionfish in the U.S. Virgin Islands. Therefore, we present further evidence of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 the potential CFP hazard that lionfish may pose in additional areas of the Caribbean.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations